The Relevance of the Concept of Isti'anah from the Perspective of KH. Zaini Mun'im's Interpretation of Bil Imla' in Facing the Temptation of Materialism in the Modern Era - Luthviyah Romziana; Sulastri Sulastri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The growing materialism among today's youth often leads to a misunderstanding of success, which is measured only in material terms. This is a challenge in creating a balanced mindset between worldly and ukhrawi life. This study aims to analyze the relevance of the concept of isti'anah according to the interpretation of Bil Imla' by KH Zaini Mun'im in overcoming the temptation of materialism in adolescents. The approach used in this study is a literature review with interpretation analysis and a review of related literature. The results of the study show that the concept of isti'anah teaches Muslims, especially teenagers, to ask for help only from Allah SWT, which can be a solution to avoid the temptation of materialism. This concept also emphasizes the importance of a balance between temporal and spiritual pursuits, by always linking God's help through patience, prayer, and spiritual awareness. In conclusion, the interpretation of Bil Imla' can be an effective guideline to help adolescents form a more balanced mindset, avoid excessive materialism, and increase closeness to Allah in achieving true success.